Prophylaxis in children with haemophilia in an evolving treatment landscape. Issue 6 (21st September 2021) - Mancuso, Maria Elisa; Male, Christoph; Kenet, Gili; Kavakli, Kaan; Königs, Christoph; Blatný, Jan; Fijnvandraat, Karin
Abstract: Introduction: For children with haemophilia, early initiation of prophylaxis is crucial to prevent life‐threatening bleeds and maintain joint health throughout life. Options for prophylaxis have recently increased from replacement therapy with standard or extended half‐life coagulation factor products to include other haemostasis products, such as the non‐replacement therapy emicizumab. Aim: To review key factors that determine the choice of prophylaxis in young children. Methods: Key clinical questions on the implementation of prophylaxis for haemophilia in children were identified and PubMed was searched for evidence supporting guidance on the implementation of prophylaxis. Results: The results of the literature search and the practical experience of the authors were used to build consensus on when to start prophylaxis, the pros and cons of the products available to guide the choice of product, and practical aspects of starting prophylaxis to guide the choice of regimen. Conclusions: In this era of increasing therapeutic choices, available information about the range of treatment options must be considered when initiating prophylaxis in young children. Parents or care givers must be sufficiently informed to allow informed shared decision making. Although plentiful data and clinical experience have been gathered on prophylaxis with clotting factor replacement therapy, its use in young children brings practical challenges, such as the need for intravenous administration. In contrast, our relatively brief experience and limited data with subcutaneously administered non‐replacement therapy (i.e., emicizumab) in this patient group imply that starting emicizumab prophylaxis in young children requires careful consideration, despite the more convenient route of administration.